Desain Model Pendayagunaan Zakat Berbasis Kebutuhan Mustahik di Kabupaten Sorong - Ekarina Katmas (ITB AAS INDONESIA Surakarta, 2023)
The utilization of zakat in minority Muslim areas is interesting to study. This study aims to explore a model of zakat utilization based on the needs of mustahik in Sorong district. The intended utilization model refers to the allocation of zakat funds given to mustahik. This research uses descriptive qualitative method through exploratory case studies. Data collection used an interview technique on officials receiving BAZNas assistance, Sorong district. The results of this study's data analysis show that the zakat utilization model implemented by BAZNas in Sorong district includes the taqwa district, caring district, smart district, healthy district, and prosperous district. Some of these programs have not run optimally because they are limited by the availability of collected zakat funds. The average total zakat fund collected per year is only 25 million, so it is not sufficient for the implementation of the overall program both based on requests and BAZNas initiatives. The small amount of zakat funds collected indicates a lack of community participation in fulfilling zakat mal and fitrah obligations in this area.